Calibration of the ISO tapping machine for finite-element prediction tool on a wooden-base floor. Issue 3 (September 2019) - Qian, Cheng; Ménard, Sylvain; Bard-Hagberg, Delphine; Kouyoumji, Jean-Luc; Negreira, Juan
One important challenge of the wooden constructions is to achieve a high quality of acoustic insulation, especially decreasing the impact noise in the low-frequency range. In order to avoid over-designed solutions and expensive experimental tests in the design phase, reliable prediction tools are called for. This article is an initial investigation of modeling the ISO standardized tapping machine on a cross-laminated timber floor, using finite element method. The wooden-based floor was first calibrated in terms of its dynamic properties. The influence of the material properties of the cross-laminated timber floor was discussed. The force generated by the tapping machine was then introduced in the established cross-laminated timber model. The model was finally validated by comparing the simulation results with the measured accelerations.